Adaptación de la metodología de desarrollo de software scrum a equipos de un solo programador. caso: departamento de sistemas de la cooperativa de ahorro y crédito andina ltda - Arias Herrera, Jairo Fernando (2016)
The research project "Adaptation of the Methodology Software Development Scrum teams a single programmer", aims to adapt the framework of Scrum by applying best practices in its process model for implementing solutions computer in the Department of Systems credit union Andina Ltda. the evidenced issue focuses on the traditional process used for software development, because a systematic process that would ensure the effectiveness of the software didn’t follow implemented, causing the software is putting into production very functional. In the project the method of abstraction, with which the essential characteristics of Scrum for analysis and subsequent application in a case study abstracted applied. It obtained as a result defined a framework focused on computers with a single programmer, providing a systematic process based on the rules and values on which is founded Scrum. Results were applied in the development of an application called "Control of Appellations of Money" for the area of cash registers of Cooperative software product with high functional level and puts into production.